Linkage disequilibrium and effective population size in Gir cattle selected for yearling weight - Toro Ospina, Alejandra M. [UNESP]; Maiorano, Amanda Marchi [UNESP]; Curi, Rogerio A. [UNESP]; Pereira, Guilherme L. [UNESP]; Zerlotti-Mercadante, Maria Eugenia; Santos Goncalves Cyrillo, Joslaine Noely dos; Aspilcueta-Borquis, Rusbel R.; Silva, Josineudson A. de V. [UNESP] (Wiley-Blackwell, 2019)
Linkage disequilibrium (LD) plays an important role in genomic selection and mapping of quantitative trait loci (QTL). This study investigated the pattern of LD and effective population size (N-e) in Gir cattle selected for yearling weight. For this purpose, 173 animals with imputed genotypes (from 18 animals genotyped with the Illumina BovineHD BeadChip and 155 animals genotyped with the Bovine LDv4 panel) were analysed. The LD was evaluated at distances of 25-50 kb, 50-100 kb, 100-500 kb and 0.5-1 Mb. The N-e was estimated based on 5 past generations. The r(2) values (a measure of LD) were, respectively, .35, .29, .18 and .032 for the distances evaluated. The LD estimates decreased with increasing distance of SNP pairs and LD persisted up to a distance of 100 kb (r(2) = .29). The N-e was greater in generations 4 and 5 (24 and 30 animals, respectively) and declined drastically after the last generation (12 animals). The results showed high levels of LD and low N-e, which were probably due to the loss of genetic variability as a consequence of the structure of the Gir population studied.
Keywords: Bos indicus; genetic variability; linkage disequilibrium